Let $f(x) = 4x - 7$, $g(x) = (x + 1)^2$, and $s(x) = f(x) + g(x)$. What is $s(3)$?
2 answers:
s(3)=4(3)-7+(3+1)^2
s(3)=12-7+16
s(3)=21
Answer:
21
Step-by-step explanation:
We find that s(x) = 4x - 7 + (x + 1)^2. Expanding, we get s(x) = x^2 + 6x - 6. Plugging in x = 3, we have s(3) = 3^2 + 6 x 3 - 6 = 21.
Alternatively, we can compute that f(3) = 5 and g(3) = 16, so s(3) = f(3) + g(3) = 21.
You might be interested in
8-3x
Divide the whole thing by 2 so it would be y=4-1.5x
<span>x cubed +3x squared - 4x= 0
= x^3 + 3x^2 -4x = 0
=x(x^2 +3x -4) = 0
= x (x+4)(x-1) = 0
x = 0
x+ 4 = 0 then x = -4
x - 1 = 0 then x = 1
answer: x = 0, x = -4 and x = 1</span>
Answer:
Step-by-step explanation:
If anything is not clear, just ask me.
Answer:
(9×-27)
= (243×4)
= 972